Role of Toll-Like Receptors and Th Responses in Viral Myocarditis - Zheng, Shi-Yue; Dong, Jian-Zeng (Frontiers in Immunology, 2022)
Myocarditis is the common cause of sudden cardiac death in young adults and the primary cause of dilated cardiomyopathy (DCM) and heart failure (HF), of which the most common type is viral myocarditis (VMC). Toll-like receptors (TLRs) are vital to identify pathogens in vivo. TLRs promote the differentiation of naive CD4+T cells to T helper (Th) cells, activate the immune response, and participate in the pathogenesis of autoimmune and allergic diseases. Although the pathogenesis of VMC is unclear, autoimmune responses have been confirmed to play a significant role; hence, it could be inferred that VMC is closely related to TLRs and Th responses. Some drugs have been found to improve the prognosis of VMC by regulating the immune response through activated TLRs. In this review, we discuss the role of TLRs and Th responses in VMC.